MHD Hybrid Nanofluid Flow Over a Permeable Surface - Mohd Azhar, Auna; Fazlina Aman (Enhanced Knowledge in Sciences and Technology, 2024)
This current investigation is about magnetohydrodynamic (MHD) of hybrid nanofluid over a permeable surface. This study was conducted by using shooting technique in Maple as a numerical method to obtain. The transformation of a PDE to ODE using a group of similarity variables in order to solve the solution in Maple software. The impacts of several parameters such as, the heat source/sink parameter and radiation were observed in the graph and table shown. It is also can be notice that different parameters of nanofluid affect the properties of nanofluid depending on the fluid itself. This is because, the nanoparticles have the biggest role within the changes of the nanofluid such as density, viscosity, temperature and more. Skin friction coefficient and heat transfer coefficient will be analysed in this study and it reveals that skin friction and heat transfer coefficient could have a big vary of impacts to the nanofluid if the characteristics of the nanofluid were manipulated.